ETNOZOOLOGI SEBAGAI PERTANDA OLEH MASYARAKAT DAYAK SIMPAKNG DI DESA MEKAR RAYA KECAMATAN SIMPANG DUA KABUPATEN KETAPANG - Yogi, Yulius; Anwari, M Sofwan; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2019)
Dayak Simpankg comunity in Mekar village are people who still hold the values inherited by their ancestors. One of the values that they are still running up to now is using animals as a sign. The purpose of this study is to find out the species of animal used as a sign, the part used and the meaning of the sign. The method used in field data collection is by interview and the data collection technique used is the snowball sampling method. Based on the results of the interview, 15 respondents were obtained. A total of 10 species animals from 10 families, namely Wild Pig, Clouded Leopard, Brown Wood Owl, White Rumped Munia, White Rumped Shama, Orange Bellied Flowerpecker, White Breasted Waterhen, Asian Paradise Flycatcher, Asian Toad and Flat Tailed Gecko are utilized by Dayak Simpakng comunity. Some parts that are used are sounds, animals that suddenly enter the house, and animals that pass above the head.Keyword : Dayak Simpakng, Etnozoology, Pertanda